Regulation of germinal center B-cell differentiation - Zhang, Yang; Garcia-Ibanez, Laura; Toellner, Kai-Michael (Immunological reviews, 2016)
Summary Germinal centers (GC) are the main sites where antigen‐activated B‐cell clones expand and undergo immunoglobulin gene hypermutation and selection. Iterations of this process will lead to affinity maturation, replicating Darwinian evolution on the cellular level. GC B‐cell selection can lead to four different outcomes: further expansion and evolution, apoptosis (non‐selection), or output from the GC with differentiation into memory B cells or plasma cells. T‐helper cells in GC have been shown to have a central role in regulating B‐cell selection by sensing the density of major histocompatibility complex (MHC):peptide antigen complexes. Antigen is provided on follicular dendritic cells in the form of immune complex. Antibody on these immune complexes regulates antigen accessibility by shielding antigen from B‐cell receptor access. Replacement of antibody on immune complexes by antibody generated from GC‐derived plasma cell output will gradually reduce the availability of antigen. This antibody feedback can lead to a situation where a slow rise in selection stringency caused by a changing environment leads to directional evolution toward higher affinity antibody.